AI in Cloud-Based Digital Transformation of Smart Cities - Kayani, MOHSIN (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
Artificial Intelligence (AI) and cloud platforms now sit at the center of how cities plan and run services. Rather than reacting to congestion, energy demand, or service failures, departments can anticipate them by analyzing streams of urban data. This study maps the field by combining a bibliometric review with policy analysis. Using the Scopus database and VOSviewer 1.6.20, 376 peer-reviewed items published between 2020 and 2025 were analyzed to trace publication growth, collaboration networks, and thematic clusters. Four domains recur: (1) AI-cloud infrastructure, (2) urban sustainability and mobility, (3) governance and ethics, and (4) smart-services innovation. High-income economies—especially China, the United States, and the United Arab Emirates—lead output and cross-institutional collaboration, while participation from the Global South remains limited. Human-centered design, open-data governance, and adaptive regulation are essential if AI-cloud systems are to support equitable outcomes aligned with UN SDG 11 and Saudi Vision 2030.